A critical geopolitics transformed by the Covid-19 pandemic - Preciado Coronado, Jaime Antonio (2020)
COVID-19 showed, without precedent, a health, economic, political and environmental crisis, around which space-time was compressed from a simultaneity creating a global and systemic “we”; the pandemic is lived in real time globally connected, and paradoxically, fragmented by national histories of inequality and social and environmental injustice. The magnitude of the COVID-19, takes the role of detonator of a new geopolitics that radically disrupts the world order, that reinforces the national state as pivot of the “governmentality” and that resignifies the local powers, particularly the corporal sphere, of subjective and intersubjective feelings and emotions. Where uncertainty and chaos are debated between the old that dies and the living that replaces it, we are before the (re)emergence of geopolitical imaginaries that update that famous slogan “Another world [of universalist particularisms, better than the current one] is possible”.